1976
DOI: 10.1172/jci108509
|View full text |Cite
|
Sign up to set email alerts
|

Studies on the mechanisms of food-stimulated gastric acid secretion in normal human subjects.

Abstract: A B S T R A C T Liquid test meals were infused into the stomach and acid secretion was measured by intragastric titration at pH 5.0. Acid secretion after 500 or 750-ml sodium chloride meals was two to three times higher than basal secretion rates and was equivalent to 25-30% of the peak acid output in response to histamine. Since these meals did not cause a rise in serum gastrin concentration, it is assumed that they stimulate acid secretion by causing distention of the body and fundus of the stomach. Compared… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
63
0

Year Published

1980
1980
2019
2019

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 145 publications
(68 citation statements)
references
References 9 publications
5
63
0
Order By: Relevance
“…Among these, GRP has a stimulatory action on gastrin release from G cells [21] . Gastrin released by GRP stimulation is the most important physiological secretagogue and it has a primary role in postprandial acid secretion [22] . Gastrin stimulates acid secretion via enterochromaffin-like cells (ECL cell) [23] .…”
Section: Ghrelin and Histamine Releasementioning
confidence: 99%
See 1 more Smart Citation
“…Among these, GRP has a stimulatory action on gastrin release from G cells [21] . Gastrin released by GRP stimulation is the most important physiological secretagogue and it has a primary role in postprandial acid secretion [22] . Gastrin stimulates acid secretion via enterochromaffin-like cells (ECL cell) [23] .…”
Section: Ghrelin and Histamine Releasementioning
confidence: 99%
“…Gastrin is known to be released into the circulation in response to food [31] , and to play an important roles in increasing postprandial acid secretion [22] , and to exert activity on ECL cells [23] . It was shown that vagotomy did not affect the maximal response of acid secretion to gastrin administration thus indicating that the action of gastrin was not primarily dependent on vagal nerve [32] .…”
Section: Ghrelin and Gastrin In The Mechanism For The Regulation Of Gmentioning
confidence: 99%
“…Once the menasurement of postprandial acid secretion in huma-n subjects became possible by the method of intragastric titration (3), attempts were made to correlate acid secretion with postprandial serumn gastrin concentrattioins, but no correlations were founld (3,4). This, however, is not unexpected, as these stuidies were based on the acid and gastrin responses to a single level of stimulation by a standard meal in different individuals.…”
Section: Introductionmentioning
confidence: 99%
“…fasting gastric pH values in healthy individuals are 1 to 3, and calcium is highly soluble in this environment. Because dietary protein is known to increase gastric acid secretion, (10)(11)(12) we decided to study the effect of a PPI in the setting of a highprotein diet, thereby maximizing gastric acid output. When acidic gastric chyme enters the duodenum, it stimulates secretin production, causing pancreatic and intestinal epithelial secretion of bicarbonate.…”
Section: Discussionmentioning
confidence: 99%
“…The study employed a crossover design in which each study subject served as his or her own control, thereby eliminating the confounding effect of interindividual variation on calcium absorption. We chose to use a high-protein diet for all interventions in our study because available data indicate that this would augment gastric acid production and intestinal calcium absorption, (10)(11)(12)(13) allowing us the best opportunity to quantify the contribution of gastric acid to calcium absorption.…”
Section: Introductionmentioning
confidence: 99%